Web 2.0 as a new channel for innovation diffusion: The case study of renewable energy products - Mrabet, Rim Gharbi (2016)
Nowadays, social web and social media are considered as new communication’ channels that enable the diffusion of new products and innovations, such as: renewable energy products. In addition, renewable energies become the new alternative source of energy that insures environmental benefits, economic returns and social welfare.Hence, we will focus in this study on the impact of the use of web 2.0 and social networks in the diffusion of renewable energy products.